Tricuspid Valve Endocarditis With Group B Streptococcus After an Elective Abortion: The Need for New Data - Erica E. Palys; John Li; Paula L. Gaut; W. David Hardy (Hindawi Limited, 2006)
Streptococcus agalactiae, commonly known as Group B streptococcus (GBS), was originally discovered as a cause of bovine mastitis. GBS colonizes the genital tract of up to 40% of women and has become a major pathogen in neonatal meningitis. GBS endocarditis is thought to be an uncommon manifestation of this infection and carries a higher mortality compared to other streptococcal pathogens. Studies have shown that endocarditis after abortion has an incidence of about one per million. However, this figure was published prior to routine use of echocardiography for diagnosis. The American Heart Association has recently declared transesophageal echocardiography the gold standard for endocarditis diagnosis. This case report illustrates that, given the potentially devastating consequences of endocarditis, there is a need for updated studies to adequately assess the true incidence of this infection. Pending the outcome of these studies, routine GBS screening and prophylactic antibiotics prior to abortion should be recommended.